ANALISIS MARGIN LABA BERSIH TERHADAP PENCAPAIAN PENINGKATAN LABA ATAS PENDAPATAN YANG DIPEROLEH PADA USAHA LAUNDRY (STUDI KASUS USAHA DI MAKASSAR) - SATRIANI SATRIANI; MUFTI KHAERIAH B; WAHYU MARDIASTUTI; HASANUDDIN HASANUDDIN; MUHAMMAD AKBAR (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
Net Profit Margin or NPM is the ratio to find out the profit obtained from net sales by companies or small businesses by comparing net income and net sales. The purpose of this research is to analyze the Net Profit Margin in the Laundry business 57 in 2019 Makassar city. This research uses descriptive quantitative research methods. The results of this study indicate that the Net Profit Margin or NPM laundry 57 in 2019 is very good, namely in the range of 69.10% -81.22%. In January to June, there was an increase and decrease in the Net Profit Margin ratio, namely the percentage of 72.9%, 69.10%, 75.8%, 74.10%, 81, 22% and 80.6%. In July and August, it decreased with the same percentage of the NPM ratio, namely 71.5%. And NPM in September to December 2019 has increased continuously with the NPM ratio, namely: 72.2%, 73.1%, 74.8%, and 81.2%.